Exploring the role of exosomal MicroRNAs as potential biomarkers in preeclampsia - Shan, Yuping; Hou, Bo; Wang, Jingli; Chen, Aiping; Liu, Shiguo (Frontiers in Immunology, 2024)
The complex pathogenesis of preeclampsia (PE), a significant contributor to maternal and neonatal mortality globally, is poorly understood despite substantial research. This review explores the involvement of exosomal microRNAs (exomiRs) in PE, focusing on their impact on the protein kinase B (AKT)/hypoxia-inducible factor 1-α (HIF1α)/vascular endothelial growth factor (VEGF) signaling pathway as well as endothelial cell proliferation and migration. Specifically, this article amalgamates existing evidence to reveal the pivotal role of exomiRs in regulating mesenchymal stem cell and trophoblast function, placental angiogenesis, the renin-angiotensin system, and nitric oxide production, which may contribute to PE etiology. This review emphasizes the limited knowledge regarding the role of exomiRs in PE while underscoring the potential of exomiRs as non-invasive biomarkers for PE diagnosis, prediction, and treatment. Further, it provides valuable insights into the mechanisms of PE, highlighting exomiRs as key players with clinical implications, warranting further exploration to enhance the current understanding and the development of novel therapeutic interventions.